SiGe BicMOS Building Blocks for 5G Applications - Calzona, Domenico; Crupi, Felice; Boccia, Luigi; Arnieri, Emilio (My University, 2019)
SiGe BiCMOS semiconductor technology has been increasing its application domain especially for the development of complex microwave monolithically integrated circuits (MMIC) required for modern telecommunication systems. This thesis presents a set of building blocks developed in different SiGe BiCMOS technologies for reconfigurable antenna applications. The developed blocks are oriented to the implementation of electronically scanned phased arrays or of switched beam antenna systems. The red thread that links the different topics is the next generation mobile communication systems, namely 5G systems. However, 5G networks instead of providing specific requirements for each block are employed as an application context that is adopted to provide a real employment scenario for each device proposed in this work. The thesis is organized as follows. In the first chapter, an overview about development opportunities of 5G technology is illustrated. In the second chapter, a brief introduction in the world of MMIC and SiGe technology has been provided. In the third chapter, beam-forming networks are dealt introducing the design of an 8x8 Butler matrix and a Wilkinson combiner/divider in SiGe BiCMOS technology. In the fourth chapter, a quarter wavelength resonant filter phase shifter is presented. An innovative technique to realize a phase shifter using the peculiarity of the pass-band filters. In the fifth chapter, it is presented a study on metamaterial structures based on Split Ring Resonators integrated with on-chip Coplanar Wave guides. In the last chapter, a FDD technique is illustrated along with the design of a Duplexer in K/Ka-band with High/Low pass filter.
Dottorato di Ricerca in Information and Communication Technologies, Ciclo XXX
Keywords: Integrated circuits; Metal oxide semiconductors